An in vitro study on the degradation of multispecies biofilm of periodontitis-related microorganisms by bovine trypsin - Zhou, Jing; Meng, Xinhui; Han, Qunchao; Huang, Yinxue; Huo, Lijun; Lei, Yayan (Frontiers in Microbiology, 2022)
To investigate the degradation effect of bovine trypsin on multispecies biofilm of periodontitis-related bacteria and to provide an experimental reference for exploring new methods for controlling biofilms of periodontitis-related microorganisms, the multispecies biofilm of periodontitis-related microorganisms was established. Standard strains of Porphyromonas gingivalis, Fusobacterium nucleatum subsp. polymorpha, Actinomyces viscosus, and Aggregatibacter actinomycetemcomitans were co-cultured to form the biofilm. The experimental groups were treated with bovine trypsin, distilled water was applied as the blank control group, and phosphate saline buffer (pH = 7.4) as the negative control group. Morphological observation and quantitative analysis of extracellular polymeric substances (EPS), live bacteria, and dead bacteria were conducted using a laser confocal microscope. The morphological changes of EPS and bacteria were also observed using a scanning electron microscope. The results of morphological observations of modeling were as follows. EPS aggregated as agglomerates, and bacteria flora were wrapped by them, showing a three-dimensional network structure, and channel-like structures were inside the biofilm. Live bacteria were distributed on the surface of the EPS or embedded in them, dead bacteria aggregated between live flora and the bottom layer of biofilms. After being treated with bovine trypsin, the three-dimensional network structure and the channel-like structure disappeared, and the EPS and live and dead bacteria decreased. Quantitative analysis results are as follows. When biofilm was treated for 30 s, 1 min, and 3 min, the minimum effective concentrations of bovine trypsin to reduce EPS were 2 mg/ml (P < 0.05), 0.5 mg/ml (P < 0.05), and 0.25 mg/ml (P < 0.05), respectively. The minimum effective concentrations of bovine trypsin to reduce the live or dead bacteria were 2 mg/ml (P < 0.05), 0.5 mg/ml (P < 0.05), and 0.5 mg/ml (P < 0.05), respectively. There was no significant difference in the ratio of live/dead bacteria after the biofilm was treated for 30 s with bovine trypsin at the concentration of 0.25, 0.5, 1, and 2 mg/ml (P > 0.05), and the minimum effective concentration to reduce the ratio of live bacteria/dead bacteria was 0.25 mg/ml (P < 0.05) after treatment for 1 min and 3 min. Therefore, bovine trypsin can destroy biofilm structure, disperse biofilm and bacteria flora, and reduce the EPS and bacterial biomass, which are positively correlated with the application time and concentration.